Effect of Clove Flower and Leaf Extracts on Sedation in Hybrid Catfish - วงศ์เผ่าสกุล สุริยเมธินท์; โพธิ์ศรี สุพรรณ; สุพรรณ สุทธวรรณ; พุทธกาล นพรัตน์ (Progress in Applied Science and Technology, 2017)
The extracts from cloves (Syzygium aromaticum (L.) Merr. & L.M.Perry) flowers and leaves are widely used in dental care as an antiseptic and analgesic agent due to its antibacterial effect against a large number of bacteria. The aims of this study were to: (1) reveal the chemical composition of clove flower and leaf extracts using GC-MS. and (2) evaluate the sedative and anesthetic effects of the extracts on aquaculture transportation. The juvenile catfishes with an average length of 7-10 cm and average weight of 8-12 g, and four extracted sample concentrations of 50, 100, 150 and 200 mg/L were used to assess the induction time from sedation and recovery. The chemical composition identified using GC-MS analysis comparing with pure eugenol, a standard agent revealed that eugenol was a major constituent of the extracts. It was 79.62% from leaf extract followed by 62.53% from flower extract. Clove flower extract induced sedation of hybrid catfish at 20.17 ± 0.0.970, 13.33 ± 0.516, 4.67± 0.516, 3.33± 0.258 min, respectively. The recovery of hybrid catfish showed of 67.50 ± 0.880, 48.67± 0.931, 67.50 ± 1.696 and 112.50 ± 1.754 min, respectively. Clove leaf extract induced sedation of hybrid catfish at 37.83 ± 0.585, 22.33 ± 0.931, 20.83 ± 0.585, 17.17 ± 0.585 min, respectively. For the recovery of hybrid catfish showed of 2.806 ± 1.204, 3.557 ± 0.914, 56.33 ± 1.125, and 70.83 ± 0.917 min, respectively. In addition the optmal concentration producing total loss of balance and response to external stimuli with shorter induction time was the flower extract fallowed by leaf extract at 50 and 100 mg/L with a duration time of 20.17 ± 0.970 and 22.33 ± 0.931 min, respectively.